1994
DOI: 10.1152/ajpendo.1994.267.1.e77
|View full text |Cite
|
Sign up to set email alerts
|

[Ca2+]i signaling in pregnant human myometrium

Abstract: The purpose of the present study was to determine the changes in intracellular ionized calcium concentration ([Ca2+]i) or [Ca2+]i sensitivity accompanying spontaneous and agonist-induced contraction of human myometrium at term pregnancy, as well as to quantify the response to three prototypical agonists: 1) oxytocin, 2) vasopressin, and 3) phenylephrine. Uterine biopsies were obtained at the time of cesarean section from patients who delivered at or near full-term gestation. These preparations were used to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…It was suggested that desensitization of MLCK by phosphorylation after the first second following initiation of contraction causes a decrease in the rate of MLC phosphorylation and force production. Similar findings were obtained when the steady-state and transient C Ca,i vs. force relationships were investigated in strips of human pregnant myometria during spontaneous and agonist-induced contractions (22). Experiments with strips of pregnant and nonpregnant human myometria also revealed that MLC phosphorylation during contraction was lower in pregnant compared with nonpregnant tissue, while the amount of generated stress per MLC phosphorylation level was higher in the pregnant myometrial tissue (29).…”
supporting
confidence: 75%
“…It was suggested that desensitization of MLCK by phosphorylation after the first second following initiation of contraction causes a decrease in the rate of MLC phosphorylation and force production. Similar findings were obtained when the steady-state and transient C Ca,i vs. force relationships were investigated in strips of human pregnant myometria during spontaneous and agonist-induced contractions (22). Experiments with strips of pregnant and nonpregnant human myometria also revealed that MLC phosphorylation during contraction was lower in pregnant compared with nonpregnant tissue, while the amount of generated stress per MLC phosphorylation level was higher in the pregnant myometrial tissue (29).…”
supporting
confidence: 75%
“…Strips were mounted vertically in 50-ml tissue baths, and tension was recorded with an isometric tension transducer (Grass Instrument Division, West Warwick, RI). Experiments were performed at 37°C as previously described (34). Preparations were allowed to equilibrate for 1 h before initiation of experiments.…”
Section: Methodsmentioning
confidence: 99%
“…It is clear, however, that the primary trigger for human myometrial contractions (spontaneous and agonist induced) is a rise in intracellular calcium (Szal et al 1994;Luckas et al 1999). The relative contribution of calcium entry and calcium release from intracellular stores to the rise in intracellular calcium, however, is uncertain and is the focus of ongoing studies in our laboratory and others.…”
Section: Role Of Calcium In Initiating Contractionsmentioning
confidence: 99%